The (Un)Repressed Memory of Poznań June in 1958–80 - Jaśniak, Paulina (Sensus Historiae, 2025)
It is commonly agreed that the Poznań June began on June 28, 1956, and ended with a speech of Władysław Gomułka in the Cegielski Metal Factories (HCP) in Poznań in 1957. The First Secretary of the Central Committee of the Polish United Workers’ Party appealed to draw a “mourning curtain of silence” over the demonstration. Since then, the topic, uncomfortable for the communist authorities, was omitted from public discourse. However, local community remembered and demanded respect for the dead and their families. This article focuses on the ways of commemoration of the Poznań June in the years 1958-80, i.e. at the most difficult moment. Modest attempts made by the Catholic Church or the inhabitants posed numerous problems for the authorities, only to explode with double force in 1976. In the years 1976-80, an organized opposition appeared and loudly demanded the commemoration of the events of 1956.